Intermittent hypoxic training - Hellmans, J.; Hamlin, M. (2004)
Altitude training was first introduced into the western world on a larger scale following the Mexico Olympics (1964). At the time it was noticed that endurance athletes suffered when competing in the Games and they were unable to get close to their best times. Athletes who had acclimatized prior to the games fared much better. More significantly when returning to sea-level to compete following the games, many personal best times and world records were set. For a long time however scientist found little evidence of benefits from altitude training despite significant perceived benefits experienced by athletes and coaches. There are different expectations around altitude training, between the coach/athlete and the scientist. For the coach and athlete the proof in the experience is enough, while scientists are not satisfied until benefits are proven, double blind and without doubt. Scientists are still arguing the benefits of conventional altitude training (live high/train high). The high/low model has been given the thumbs up by athletes, coaches and scientists, while the benefits of altitude simulation are still hotly debated. Coaches and athletes all over the world continue to experiment with the different methods of altitude exposure. In the mid 1990`s altitude training became an official part of the New Zealand Triathlon High Performance Programme. Initial live high/train high camps in Northern America and Europe were followed by live high/train low camps, mainly in Northern America. In recent years an altitude training facility has been discovered in the South Island of New Zealand, which is now used regularly by triathletes. The facility (www.snowfarm.nz.com) lends itself to the live high/train low model as well as to the live high/train high and train low model. Altitude simulators can be used in addition to artificially increase hypoxic intensity.